Pretrial Risk Assessment in Virginia: The Virginia Pretrial Risk Assessment Instrument (2009) - Marie VanNostrand, Ph.D., and Kenneth J. Rose (My University, 2016)
Consistent with the Code of Virginia, the Virginia Department of Criminal Justice Services in partnership with the Virginia Community Criminal Justice Association and Luminosity, Inc., developed, implemented, and validated the Virginia Pretrial Risk Assessment Instrument (VPRAI) for use by pretrial services agencies. An overview of pretrial risk assessment generally, the development and validation of the VPRAI, and instructions for instrument completion are provided in this report.

Reseña: Consistent with the Code of Virginia, the Virginia Department of Criminal Justice Services in partnership with the Virginia Community Criminal Justice Association and Luminosity, Inc., developed, implemented, and validated the Virginia Pretrial Risk Assessment Instrument (VPRAI) for use by pretrial services agencies. An overview of pretrial risk assessment generally, the development and validation of the VPRAI, and instructions for instrument completion are provided in this report.